The Effect of Student Participation through the Use of Online Learning Platforms in improving student learning outcomes - Ni Wayan Karmini; I Made Yudabakti; Desak Nyoman Seniwati; Korlina Makulua; Natanel Burnama (International Journal of Language and Ubiquitous Learning, 2024)
Background. Along with the development of the times, the learning process in education is increasingly advanced. Especially in this digital era, where the use of online learning platforms is rampant, it is used as an alternative to improve learning effectiveness. The main aspect of using this online learning platform is student participation. Purpose. The purpose of this study is to determine the effect of student participation on the use of online learning platforms in terms of improving student learning outcomes. Method. The method used in this study uses a quantitative approach. The research data was obtained from the results of questionnaire filling by students. The sample used in this study is students in schools that use online learning platforms. Results. The results of this study show that with student participation in learning using online learning platforms can improve student learning outcomes. On average, students provide active participation when learning takes place using the online learning platform. Conclusion. The conclusion of this research is that there is student participation through the use of online learning platforms which has a positive influence on students in terms of improving student learning outcomes continuously. Therefore, an educator must be more able to encourage students to participate more actively in learning and introduce students to online learning platforms. The limitation of this study is that researchers did not go directly to schools to conduct research but rather by distributing questionnaires.